Influence of family factors on the incidence of lower respiratory illness during the first year of life. Issue 4 (December 1976) - Leeder, S R; Corkhill, R; Irwig, L M; Holland, W W; Colley, J R
Abstract : In a study of a cohort of over 2000 children born between 1963 and 1965, the incidence of bronchitis and pneumonia during their first year of life was found to be associated with several family factors. The most important determinant of respiratory illness in these infants was an attack of bronchitis or pneumonia in a sibling. The age of these siblings, and their number, also contributed to this incidence. Parental respiratory symptoms, including persistent cough and phlegm, and asthma or wheezing, as well as parental smoking habits, had lesser but nevertheless important effects. Parental smoking, however, stands out from all other factors as the one most amenable to change in seeking to prevent bronchitis and pneumonia in infants.